Extreme total column ozone events and effects on UV solar radiation at Thessaloniki, Greece - Fragkos, Konstantinos; Bais, Alkiviadis F.; Fountoulakis, I.; Balis, Dimitris S.; Tourpali, Kleareti D.; Meleti, Charickleia; Zanis, Prodromos (My University, 2016)
Thirty years of total ozone column (TOC) measurements conducted by a Brewer spectrophotometer, operating in Thessaloniki (40.6°) since March 1982, have been analyzed using the statistical extreme value theory for the identification of extreme TOC events. About 12 % of the total number of days with TOC measurements were identified as extreme-low and ∼15 % as extreme-high events. The influence of the extreme-low events on the annual mean TOC values is up to ∼18 DU, while the extreme-high events show lower impact (up to 12 DU). Removing the extreme events from the time series results in smoother year-to-year variability and reduction of the small long-term linear trend (−0.08 %/year) by a factor of 2. Furthermore, we examined the impact of the extreme events on the noon erythemal irradiance under clear skies, and we provide evidence that even under extreme-low TOC conditions, the UV radiation levels are determined to a great extent by the aerosol optical depth. Although the influence of aerosols is evident during all seasons, for spring and summer, the sensitivity of UV radiation is larger, probably due to the different nature of the aerosols over Thessaloniki during these seasons.
Keywords: Central Macedonia; Greece; Thessaloniki; aerosol; extreme event; solar radiation; total ozone; ultraviolet radiation